(untitled) (Bangladesh Journal of Pharmacology, 2016)
The aim of study was to investigate the potential neuroprotective effects of Kombucha on cerebral damage induced by ischemia in rats (n=99). Cerebral infarct volume in the ischemic rats received Kombucha solution showed no significance alteration. However, the permeability of blood-brain barrier significantly decreased in both ischemic rats received 15 mg/kg Kombucha tea and Sham group. In addition, brain water content in the ischemic groups treated with Kombucha solution was significantly higher than the Sham group, although right hemispheres in all of the treated groups illustrated higher brain water content than the left ones. Brain antioxidant capacity elevated in the ischemic rats treated with Kombucha and in the Sham group. Brain and plasma malondialdehyde concentrations significantly decreased in both of the ischemic groups injected with Kombucha. The findings suggest that Kombucha tea could be useful for the prevention of cerebral damage. Video Clip of Methodology: Induction of brain ischemia: 5 min 19 sec Click to watch